Prinsip Itikad Baik Terhadap Merek MS Glow - Rachman, Taslim Abd.; Alauddin, Rusdin; Alwan, Sultan (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
Legal protection is an important aspect that needs to be considered in the controversy between MS Glow and PS Glow trademarks. PT Kosmetika Global Indonesia, the MS Glow brand holder that has registered its brand with the Director General of Intellectual Property Rights, requires adequate legal protection. The public sees that the products of the MS Glow brand are better known than the products of the PS Glow brand, and there is a view that PS Glow is trying to hijack the popularity of MS Glow. Through normative juridical legal research, it was found that in the context of the principle of good faith, MS Glow is entitled to legal protection as a brand owner. The brand owner has the exclusive right to the use of its brand and the government is responsible for ensuring this protection. The judge's decision in the dispute between the MS Glow and PS Glow trademarks (Decision Number 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga.Sby) has fulfilled the principle of legal certainty. The judge refers to Law Number 20 Year 2016 on Trademark Registration and Geographical Indications as well as the principle of